Competitive strategies for water availability in two Mediterranean Quercus species - Nardini, A.; Gullo, M. A. Lo; Salleo, S. (Plant, Cell & Environment, 1999)
Competition for water availability was studied in a mixed natural stand of Quercus suber L. and Quercus cerris L. growing in Sicily by measuring diurnal changes of leaf conductance to water vapour (gL), water potential (ΨL) and relative water content (RWC) in April, July and October 1997 as well as the seasonal changes in root hydraulic conductance per unit leaf surface area (KRL). Quercus cerris behaved as a drought-tolerant species, with strong reductions of KRL, ΨL, and RWC in the summer. By contrast, Q. suber appeared to withstand summer drought by an avoidance strategy based on reducing gL, maintaining ΨL and RWC high and KRL at the same level as that measured in the spring. A ‘conductance ratio’ (CR) was calculated in terms of the ratio of gL to KRL. Seasonal changes of this ratio contrasted in the two species, thus suggesting that Q. suber and Q. cerris did not really compete for available water. In the summer, when Q. suber was extracting water from the soil to maintain high leaf hydration, Q. cerris had restricted water absorption, thus suffering drought but tolerating its effects. The possibility that cohabitation of drought-tolerant with drought-avoiding species can be generalized is also discussed.
Keywords: leaf conductance; leaf water status; Quercus cerris (Turkey Oak); Quercus suber (cork oak); root hydraulic conductance.

Competitive strategies for water availability in two Mediterranean Quercus species - Nardini, A; Gullo, M A Lo; Salleo, S (Plant, Cell & Environment, 1999)
Competition for water availability was studied in a mixed natural stand of Quercus suber L. and Quercus cerris L. growing in Sicily by measuring diurnal changes of leaf conductance to water vapour (gL), water potential (ΨL) and relative water content (RWC) in April, July and October 1997 as well as the seasonal changes in root hydraulic conductance per unit leaf surface area (KRL). Quercus cerris behaved as a drought-tolerant species, with strong reductions of KRL, ΨL, and RWC in the summer. By contrast, Q. suber appeared to withstand summer drought by an avoidance strategy based on reducing gL, maintaining ΨL and RWC high and KRL at the same level as that measured in the spring. A ‘conductance ratio’ (CR) was calculated in terms of the ratio of gL to KRL. Seasonal changes of this ratio contrasted in the two species, thus suggesting that Q. suber and Q. cerris did not really compete for available water. In the summer, when Q. suber was extracting water from the soil to maintain high leaf hydration, Q. cerris had restricted water absorption, thus suffering drought but tolerating its effects. The possibility that cohabitation of drought-tolerant with drought-avoiding species can be generalized is also discussed.
Keywords: leaf conductance; leaf water status; Quercus cerris (Turkey Oak); Quercus suber (cork oak); root hydraulic conductance.

Exchange of atmospheric formic and acetic acids with trees and crop plants under controlled chamber and purified air conditions - Kesselmeier, J; Bode, K; Gerlach, C; Jork, E.-M (Atmospheric Environment, 1998)
We investigated the exchange of formic and acetic acids between the atmosphere and various tree species such as beech (Fagus sylvatica L.), ash (Fraxinus excelsior L.), spruce (Picea abies L.) Karst, holm oak (Quercus ilex L.), and birch (Betula pendula L.). and some crop-plant species such as corn (Zea mays, var. Banjo), pea (Pisum sativum, var. Solara), barley (Hordeum vulgare, var. Igri) and oat (Avena sativa, var. Wiesel). All experiments were done with dynamic enclosures ßushed with puriÞed oxidant-free air, containing only low or controlled amounts of the two acids. SigniÞcant and light-triggered emission of both acids from all tree species was observed. For one tree species (ash) a seasonal large increase in fall due to early leaf decomposition was found. The standard emission factors (30¡C and PAR"1000 kmol m2 s~1) given as (nmol m~2 min~1) for acetic and formic acids, respectively, were 8.1 and 29.7 (ash, autumn), 1.0 and 3.3 (ash, summer), 0.9 and 1.4 (beech), 0.7 and 1.45 (spruce), 1.9 and 2.4 (Holm oak) and 1.7 and 6.7 (birch). Rough estimation of global annual emissions range between 20 and 130 Gmol formic acid and 10 and 33 Gmol acetic acid. These numbers reßect a 15Ð30% contribution by forest emissions to the continental organic acid budget. As compared to the global total NMHC emissions low molecular weight organic acids are of minor importance. In contrast to the trees, none of the crop-plant species investigated showed an emission, but always a clear deposition of both acids. Both emission from trees as well as uptake by the agricultural plants could be related to transpiration rates and leaf conductances
Keywords: acetic acid; assimilation; Atmosphere; crop plants; exchange of volatile organic compounds; formic acid; leaf conductance; organic acids; Plants; Transpiration; Trees

Sclerophylly and Plant Water Relations in Three Mediterranean Quercus Species - Salleo, S; GULLO, M A L O (Annals of Botany, 1990)
The possible role in drought resistance played by sclerophylly was studied in the Mediterranean oaks Quercus ilex, Q. suber and Q. pubescens. Studies were conducted on leaves at 30, 50 and 80% of their final surface area, as well as on mature leaves of the current year's growth in June and September and on 1-year-old leaves.Leaves of different ages of the three species showed quite different degrees of sclerophylly (DS). Q. ilex leaves reached the definitive DS of 1.75 g dm−2 during leaf expansion; Q. pubescens leaves hardened at the end of their expansion, with a final DS of 0.93 g dm−2; Q. suber showed the lowest DS of 0.76 g dm−2.Leaf conductance to water vapour (g1) of 1-year-old leaves of Q. ilex, measured in the field, showed a duration of the g1 peak values about twice that of the other two species. The minimum leaf relative water content (RWC), however, was near the same in the three species, indicating that water loss was recovered partly by Q. ilex leaves. This was apparently due to the higher bulk modulus of elasticity (max) as resulting from leaf water potential isotherms.High correlation coefficients were noted between DS and max but large changes in DS were needed to display minor changes in max. When both DS and max were correlated to the minimum RWC, an increase in DS of 133 % (corresponding to an increase in max of only 12 %) was needed to cause an increase in RWC of 2%. Therefore, sclerophylly cannot be considered as significantly related to a drought-avoiding strategy.
Keywords: Drought resistance; leaf conductance; Quercus ilex; Quercus pubescens (PG); Quercus suber L.; Relative water content; sclerophylly